(NtEORIQ RASPISANIJ I WY^ISLITELXNYE MA[INY (B/s - (NsETI(B, (Nr(B.s; (NbRUNO(B, (NdV(B.(Nl(B.s; (NaMO^KIN(B, (Nw(B.(Nm(B.s; (NkOFFMAN(B, (N|(B.(Ng(B.s; (NgOLOWKIN(B, (NbORIS aRKADXEWI^s; (NaMO^KIN(B, (Nw(B.(Nm(B.s ((NmOSKWA (B:s (NnAUKA (B,s, 1984)
(NbIBLOGRAF(B. (NS(B. 318 - 332s
Keywords: (NrASPISANIJ TEORIQs